Caribbean Report 27-01-1995 - Orr, Carol (anchor); Henry, Samuel (interviewee); Yates, Albert (interviewee); Lyons, Kirt (interviewee); Francis, Gloria (interviewee); Reid, David (correspondent); Hayes, Rosie (correspondent); Kavulich, John (interviewee); Perreira, Joseph 'Reds' (correspondent) (The British Broadcasting Corporation, 1995)
This report examines the inquest into the death of twenty-three British people who died in the Waco, Texas disaster and the open verdict which has been reached. Detective Chief Superintendent Albert Yates of the Greater Manchester Police in an interview agreed that the raid by the Bureau of Alcohol, Tobacco and Firearms was fundamentally flawed from the outset. Kirt Lyons, a lawyer representing the victims' families, filed a US$500 million civil lawsuit against the American government. In another report, two of Africa's largest banana producing countries, Cameroon and the Ivory Coast have asked for an increase in the amount of bananas they can export to Europe following the addition of three countries to the European Union this year. Gloria Francis, consultant on the Commodity Protocols with the OECS Mission in Brussels, commented on the African producers' request for an amendment to the import quota and how this may affect Caribbean banana interests. The Chairman of Britain's House Select Committee for Defence, Sir Nicholas Bonsor, pays a low-key visit to Belize. Britain and Cuba are set to sign an investment promotion and protection agreement which will pave the way for British businesses to begin investing in Cuba. Rosie Hayes reports on why Cuba is becoming increasingly attractive to American businesses. John Kavulich of the US-Cuba Trade and Economic Council, comments on this development. The final reports on the West Inddies cricket team, whose morale is high following a victory in the one-day test series in New Zealand.
1. Headlines with Carol Orr (00:00-00:29)
2. Report on the inquest into the deaths of twenty-three British people who died in the Waco, Texas disaster (00:30-01:02)
3. Interview with Samuel Henry on what this open verdict means to him (01:03-01:22)
4. Interview with the relatives of the victims of the Waco disaster (01:23-02:11)
Keywords: Waco Branch Davidian Disaster, Tex., 1993; Verdicts -- United States; Civil procedure -- United States; Banana trade -- Africa; Import quotas -- European Union countries; Africa -- Foreign economic relations -- European Union countries; Belize -- Foreign relations -- Great Britain; Great Britain -- Foreign relations -- Belize; Investments, British -- Cuba; Great Britain -- Foreign economic relations -- Cuba; Investments, American -- Cuba; United States -- Foreign economic relations -- Cuba; Cricket -- West Indies; Cricket -- Tournaments -- West Indies; Test matches (Cricket) -- New Zealand